Characterization and subcellular localization of Alongshan virus proteins - Zhao, Yinghua; Wu, Ping; Liu, Li; Ma, Baohua; Pan, Mingming; Huang, Yuan; Du, Nianyan; Yu, Hongyan; Sui, Liyan; Wang, Ze-Dong; Hou, Zhijun; Liu, Quan (Frontiers in Microbiology, 2022)
Alongshan virus (ALSV) in the Jingmenvirus group within the family Flaviviridae is a newly discovered tick-borne virus associated with human disease, whose genome includes four segments and encodes four structural proteins (VP1a, VP1b, VP2, VP3 and VP4) and two non-structural proteins (NSP1 and NSP2). Here we characterized the subcellular distribution and potential function of ALSV proteins in host cells. We found that viral proteins exhibited diverse subcellular distribution in multiple tissue-deriving cells and induced various morphological changes in the endoplasmic reticulum (ER), and NSP2, VP1b, VP2 and VP4 were all co-localized in the ER. The nuclear transfer and co-localization of VP4 and calnexin (a marker protein of ER), which were independent of their interaction, was unique to HepG2 cells. Expression of NSP1 could significantly reduce mitochondria quantity by inducing mitophagy. These findings would contribute to better understanding of the pathogenesis of emerging segmented flaviviruses.